O cotidiano em Alberto Pucheu: as relações expressivas sonoras e lexicais. - Rigoli, Elke Regina Garcia (2018)
Alberto Pucheu is a poet, teacher and literary critic, besides carrying out other activities. His work is permeated by a modern and innovative vision, while retaking the origins of classical literary texts, which makes his texts a mixture of oppositions and interactions. Checking poems in which the conditorial thread deals with daily life and its aspects, the selection was made to compose the corpus of the present study, in order to observe how such elements characterizing the day to day of the enunciator construct the expressiveness and the meaning, by such a way in which the lexical and sonorous levels of texts are combined and corroborated. It will be appreciated in this work the poems Cotidianamente, É preciso aprender a ficar submerso, Short Time and Tow-In, all part of the collection Mais cotidiano que o cotidiano (2013). The theoretical axis established for this study is granted by Discursive-Textual Stylistics, with emphasis on aspects related to Word and Sound Stylistics, whose concepts will be based on authors such as Cardoso (2009), Levin (1975), Martins (2012), Micheletti (2006), Micheletti and Sparano (2015, 2016), Riffaterre (1973), Sparano (2006), among others.